Enhanced Susceptibility of ADAP-Deficient Mice to Listeria monocytogenes Infection Is Associated With an Altered Phagocyte Phenotype and Function - Böning, Martha A. L.; Parzmair, Gerald P.; Jeron, Andreas; Düsedau, Henning P.; Kershaw, Olivia; Xu, Baolin; Relja, Borna; Schlüter, Dirk; Dunay, Ildiko Rita; Reinhold, Annegret; Schraven, Burkhart; Bruder, Dunja (Frontiers in Immunology, 2021)
The adhesion and degranulation-promoting adaptor protein (ADAP) serves as a multifunctional scaffold and is involved in the formation of immune signaling complexes. To date, only limited data exist regarding the role of ADAP in pathogen-specific immunity during in vivo infection, and its contribution in phagocyte-mediated antibacterial immunity remains elusive. Here, we show that mice lacking ADAP (ADAPko) are highly susceptible to the infection with the intracellular pathogen Listeria monocytogenes (Lm) by showing enhanced immunopathology in infected tissues together with increased morbidity, mortality, and excessive infiltration of neutrophils and monocytes. Despite high phagocyte numbers in the spleen and liver, ADAPko mice only inefficiently controlled pathogen growth, hinting at a functional impairment of infection-primed phagocytes in the ADAP-deficient host. Flow cytometric analysis of hallmark pro-inflammatory mediators and unbiased whole genome transcriptional profiling of neutrophils and inflammatory monocytes uncovered broad molecular alterations in the inflammatory program in both phagocyte subsets following their activation in the ADAP-deficient host. Strikingly, ex vivo phagocytosis assay revealed impaired phagocytic capacity of neutrophils derived from Lm-infected ADAPko mice. Together, our data suggest that an alternative priming of phagocytes in ADAP-deficient mice during Lm infection induces marked alterations in the inflammatory profile of neutrophils and inflammatory monocytes that contribute to enhanced immunopathology while limiting their capacity to eliminate the pathogen and to prevent the fatal outcome of the infection.